Ankylosing spondylitis and adenocarcinoma of the lung. Issue 3 (June 1982) - Ahern, M. J.; Maddison, P.; Mann, S.; Scott, C. A.
Abstract : A man with long standing and severe ankylosing spondylitis, treated with radiotherapy, developed a primary adenocarcinoma of the lung in an area of apical fibrosis. The significance of this is discussed and the literature reviewed.